2021
DOI: 10.18488/journal.57.2021.101.39.51
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Intracellular Greenly Fabricated Selenium Nanoparticle of Lactobacillus pentosus ADET MW861694 against Selected Food Pathogens

Abstract: This study aimed at intracellular biosynthesis of selenium nanoparticles using Lactobacillus pentosusADEB (LP) and the greenly fabricated nanoparticles were characterized based on visual observation, spectroscopy, microscopy, energy dispersive X-rays, X-ray Diffraction, and dynamic light scattering properties. The antibacterial activities of the Lactobacillus pentosusADEB selenium nanoparticles (LP-SeNPs) against selected foodborne pathogens were evaluated. A gradual change in colour from brown to reddish colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Bio-SeNPs synthesized by Lactobacillus pentosus ADET MW861694 were used to control foodborne pathogens such as Salmonella enterica subsp. arizonae , E. coli , S. enterica serotype Typhimurium, and S. aureus ( Christianah Adebayo-Tayo et al, 2021 ). Similarly, Bio-SeNPs synthesized by Lactobacillus sporogenes were used to inhibit S. aureus and E. coli ( Kaur et al, 2018 ).…”
Section: Bio-senps Antibacterial Activity Against Foodborne Pathogensmentioning
confidence: 99%
“…Bio-SeNPs synthesized by Lactobacillus pentosus ADET MW861694 were used to control foodborne pathogens such as Salmonella enterica subsp. arizonae , E. coli , S. enterica serotype Typhimurium, and S. aureus ( Christianah Adebayo-Tayo et al, 2021 ). Similarly, Bio-SeNPs synthesized by Lactobacillus sporogenes were used to inhibit S. aureus and E. coli ( Kaur et al, 2018 ).…”
Section: Bio-senps Antibacterial Activity Against Foodborne Pathogensmentioning
confidence: 99%
“…An interesting object for intracellular selenium nanoparticle production are the Gramnegative bacteria Delftia sp., known for their unique metabolic abilities to transform various pollutants; in this case, the reduction of selenite to SeNPs did not have harmful effects on the cell structure [51]. Moreover, selenium nanoparticles synthesized intracellularly using Lactobacillus pentosus were agglomerated in the surrounding medium [52]. Khoei et al showed that after the synthesis by Burkholderia fungorum, SeNPs were present both intracellularly and extracellularly.…”
Section: By Bacteriamentioning
confidence: 99%
“…In contrast, biosynthetic SeNPs derived from plants, bacteria and fungi cultured in selenium-fortified substrates have a better safety profile ( Han et al, 2021 ). The synthesized SeNPs by dos Santos Souza et al (2022) from extracts of three plants, onion ( Allium cepa ), acerola ( Malpighia emarginata ) and boldo ( Gymnanthemum amygdalinum ) inhibit Gram-positive bacteria, while SeNPs biosynthesized in cells of Lactobacillus pentosus ADEB had strong antagonistic activity against the Gram-negative bacteria Salmonella arizonae ( Adebayo-Tayo, Yusuf, & Alao, 2021 ). Meanwhile, due to its favorable biological activity and safety profile, organic selenium has also attracted much research attention recently on its bacteriostatic ability.…”
Section: Introductionmentioning
confidence: 99%